PENDIDIKAN HOLISTIK ANAK SD DITINJAU DARI TEORI REKONSTRUKSI SOSIAL JOHN DEWEY - Fauzi, Muhamad Restu (LPPM STAI DARUSSALAM LAMPUNG, 2019)
This article aims to understand the concept of holistic education for elementary school children according to John Dewey's theory of social reconstruction. Many parents think that education is the responsibility of the teacher at school so that it makes parents often off responsibility. John Dewey argues that education requires communication because humans are social creatures. Social learning is based on behavior in which children learn new things by observing other people. This research method is carried out by literature study of journals and other scientific works that have relevance to holistic education as the main source of research. The results of this study explain that holistic education is an effort to maintain overall personal development including: intellectual-emotional, physical-social, aesthetic and spiritual; According to John Dewey's theory of Social Reconstruction, holistic education for elementary school children must be supported by all elements, both from school, family and society in personality development in order to form positive personalities in children. The contribution of this research is to provide an understanding for educators, parents and the community about the function of holistic education and to clarify their respective roles.